Toward a Naturalistic Foundation of the Social Contract - Christian Cordes; Christian Schubert (Max Planck Institute for Research into Economic Systems, 2005)
This paper delivers a step toward a naturalistic foundation of the social contract. While mainstream social contract theory is based on an original position model that is defined in an aprioristic way, we endogenize its key elements, i.e., develop them out of the individuals' moral common sense. Therefore, the biological and social basis of moral intuitions are explored. In this context, a key adaptation during evolution was the one that enabled humans to understand conspecifics as intentional agents. Since these behavioral aspects are considered to be an exaptation, they are not amenable to direct genetic explanations or to rationalitybased approaches.
Keywords: P16; D71; D63; B52; A13; 330; Social contract theory; Fairness; Intentionality; Empathy; Human; Sozialvertrag; Gerechtigkeit; Evolutionsökonomik